2009
DOI: 10.1158/0008-5472.can-09-1622
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 Is Essential for Glioblastoma Cancer Stem Cell Maintenance

Abstract: Overexpression of the polycomb group protein enhancer of zeste homologue 2 (EZH2) occurs in diverse malignancies, including prostate cancer, breast cancer, and glioblastoma multiforme (GBM). Based on its ability to modulate transcription of key genes implicated in cell cycle control, DNA repair, and cell differentiation, EZH2 is believed to play a crucial role in tissue-specific stem cell maintenance and tumor development. Here, we show that targeted pharmacologic disruption of EZH2 by the S-adenosylhomocystei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
383
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(423 citation statements)
references
References 27 publications
31
383
1
Order By: Relevance
“…In addition Wang et al [8], revealed that EZH2 expression correlated with tumor aggressiveness across all cancer types and Li et al [36], showed that the most frequently overexpressed PcG gene in GBMs was EZH2 in (98.6%) and suggested that EZH2 a hopeful therapeutic target in GBMs because of the extremely high frequency of overexpression. Also similar results were optained by Suvà et al [37] and Orzan et al [38]. As regard other clinicopathologic characteristics of astrocytoma (age at diagnosis, Lobna A. Abdelsalam ; et al….…”
Section: Bmi1 and Ezh2 Expression In Astrocytoma And Non-neoplastic Bsupporting
confidence: 76%
“…In addition Wang et al [8], revealed that EZH2 expression correlated with tumor aggressiveness across all cancer types and Li et al [36], showed that the most frequently overexpressed PcG gene in GBMs was EZH2 in (98.6%) and suggested that EZH2 a hopeful therapeutic target in GBMs because of the extremely high frequency of overexpression. Also similar results were optained by Suvà et al [37] and Orzan et al [38]. As regard other clinicopathologic characteristics of astrocytoma (age at diagnosis, Lobna A. Abdelsalam ; et al….…”
Section: Bmi1 and Ezh2 Expression In Astrocytoma And Non-neoplastic Bsupporting
confidence: 76%
“…EZH2-silenced cells give rise to slow growing tumors, as has been previously shown (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 57%
“…EZH2 promotes cancer cell proliferation, anchorage-independent growth and invasiveness (13,(17)(18)(19). In vivo, EZH2 inhibition reduces tumor growth rates to various extents (18)(19)(20)(21). However, the functions of EZH2 in controlling cancer cell differentiation remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…41,42 As EZH2 depletion simultaneously abolishes both DNA damage-induced G1 and G2/M checkpoints, therapeutic targeting EZH2, as demonstrated here as a proof of concept using DZNep, in combination with standard chemotherapy, may provide a unique advantage over the existing approaches for treatment of cancer patients carrying wild-type or mutant p53. Furthermore, given a potential role of EZH2 or PRC2 in maintenance of cancer stem cells 43,44 and a recent finding showing that DNA damage-activated p21 is required for self-renewal of leukemia stem cells, 45 EZH2 inhibition might also have the potential for overcoming chemoresistance phenotype typically seen in cancer stem cells, and thereby preventing tumor recurrence after chemotherapy. Plasmids and stable cell lines.…”
Section: Discussionmentioning
confidence: 99%